Genetic, host and environmental factors associated with a high prevalence of Anaplasma marginale (2018)
Anaplasma marginale is the most prevalent vector-borne pathogen in the livestock industry in Colombia, causing economic losses of approximately USD 4.2 million per year. The present study reports the seasonal transmission patterns, genetic diversity and